The "Cooperative-Supportive" Intervention for Improving Mental Health Status among Pregnant Women - Hajmohamadi, Nahid (J Caring Sci, 2018)
Introduction: Maternal mental health during pregnancy has a major impact on fetal growth and consequently, child health. The objective of this study was to assess the effect of "Cooperative-Supportive" Intervention Program on Pregnancy. Methods: The present before and after interventional research was conducted on 114 pregnant women referring to Khoy health centers in 2014. Pregnant women were randomly divided into intervention (n=57) and control groups (n=57). The data collection tool in this research was the researcher-made questionnaire based on the Predisposing, Reinforcing and Enabling Constructs in Educational Diagnosis and Evaluation (PRECEDE) model which assessed the participants’ predisposing, enabling, and reinforcing factors. The educational interventions for enhancing pregnant women’s stress controlling skills were conducted and also practical pacifying lessons were held for the intervention group during five weeks with relaxation exercises. In order to assess health status among pregnant women, knowledge, attitude, depression, anxiety and self-efficacy were investigated by applying different scales and questioners. The questionnaires were completed before and after the interventional program. The data were analyzed, using suitable statistical tests. Results: After the intervention, the mean score of PRECEDE major components significantly increased and the total anxiety and depression scores decreased in the intervention group in comparison to those of the control group. Conclusion: The present study showed the positive impact of educational intervention programs based on PRECEED model and major components on reducing anxiety and depression, and finally mental health promotion in the studied population.